Wanita Ideal Untuk Dinikahi - Uyuni, Badrah; Fadllurrohman, Fadllurrohman (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2019)
Humans are created in pairs, they absolutely cannot be alone and live without the others. Marriage is a natural necessity for every human being that will bring harmony and happiness, a righteous woman (solehah woman) is a dream for every male, he has to know the criterias of unworthy and ideal womans before the marriage contract (‘aqd nikah) is held. It aims to create a permanent relationship between a husband and wife which can arrive the essence of marriage accordance with the purpose of marriage in Islam.